The Association Between Knowledge, Attitudes, and Smoking Practice with Relating Factors in a Junior High School - Jani, Dwi; Gunawan, Deni; Prastowo, Nawanto Agung (Jurnal Ilmu Kesehatan Masyarakat, 2020)
Smoking habit in adolescents has been increasing recently. Some factors are associated with the smoking habit. However, there are lacks of information regarding influencing factors to smoking habit in the adolescent. The study aimed to examine how knowledge, attitudes, practice, and other factors play a role in adolescents' smoking. There were 381 female and male students of a junior high school in Jakarta who participated. Influencing factors were knowledge, attitudes, practice, social influence, anti-smoking campaigns. The association between factors was analyzed using appropriate statistical tests. Most students had better knowledge, attitude, and practice. Only two students smoked cigarettes (0.5%). Gender was significantly associated with knowledge (p=0.048), social influence (p=0.000), an anti-smoking campaign (p=0.024). Knowledge had an association with social influence (p=0.002) and anti-smoking campaign (p=0.000), whereas attitudes with practice smoking (p=0.005) and anti-smoking campaign (p=0.000). Social influence was also associated with the anti-smoking campaign (p=0.000). In conclusion, students of Permai junior high school had good knowledge, attitudes, and practice of smoking. There are associations between factors that contribute to smoking habit in adolescents.